THEORETICAL ASPECTS OF DEVELOPING THE FINANCIAL STRATEGY OF THE ENTERPRISE - Saidnazarov Firdavs Abdulloevich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the essence of the company’s financial strategy, theoretical aspects of the development of the company’s strategy and conclusions are formed.